HAMP quality assurance protocol of hyperthermia systems. (September 2016) - Triantopoulou, S.; Antypas, C.; Karaiskos, P.; Armpilia, C.; Platoni, K.; Kouloulias, V.
Abstract : Introduction: Hyperthermia is an anticancer modality that uses non-ionizing radiation and performed in conjunction with radiotherapy or chemotherapy. The efficacy of hyperthermia depends on the controlled temperature increase of the tumor cells to 40– 45 °C. Treatment complications and side-effects are minimized when the temperature rise is maintained within the therapeutic range during the whole treatment session. Purpose: To establish a protocol for quality assurance (QA) of Hyperthermia equipment in Greece in order to demonstrate the need of system performance evaluation by medical physicists assuring proper operation of such equipment. Materials and Methods: The proposed protocol is the result of the Hyperthermia Committee of the Hellenic Association of Medical Physicists (HAMP) in an attempt to standardize the quality assurance procedures followed in hyperthermia applications in Greece. QA procedures proposed are based on national and international experience and on corresponding protocols of other national and international committees taking into account and incorporating the latest achievements and equipment currently used in hyperthermia applications. Results: The protocol suggests QA procedures for all types of hyperthermia methods such as superficial, intracavitary, deep-tissue heating and whole-body Hyperthermia as well as frequency for each test. Basic quality control tests include performance evaluation and testing of the correct operation of the thermometry equipment, the generator, the power measurement device, and the applicators. Tests for electrical and radiation safety are also included. The proposed necessary equipment should be accordingly calibrated and consists of a thermometer, a heat insulated container, a muscle-equivalent phantom, a power meter, a 50-ohm load, a digital frequency counter and an isotropic radiation survey meter. Conclusion: HAMP established a protocol for quality assurance of all types of Hyperthermia systems to be followed by medical physicists in Greece for efficient treatment delivery with patient and personnel safety. The protocol has been approved by the Hellenic Society of Oncologic Hyperthermia. Disclosure: No disclosure.